2015
DOI: 10.1016/j.jcv.2015.07.295
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of dengue serotype 3 virus from the cerebrospinal fluid of an encephalitis patient in Hai Phong, Vietnam in 2013

Abstract: Dengue encephalitis (DE) is characterized as unusual presentation of dengue infection. Despite the reports that DE accounts for only 1-5% of dengue cases, this disease tends to be increasingly reported to threaten global human health throughout dengue endemic areas particularly in Southeast Asia. The molecular information of clinically characterized, neurotropic dengue virus (DENV) in human beings is extremely scarce despite it playing an important role in deciphering the pathogenesis of dengue-related neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Outside of Thailand, DENV-3 genotype III also has been disseminated to other countries in Asia. DENV-3 genotype III was isolated as a minor genotype in Laos in 2012–2013 [ 76 ], and was first observed in Vietnam in 2013 [ 77 ], in Singapore in 2013 [ 78 ], and in Malaysia in 2008–2010 [ 74 ]. Our study revealed that the DENV-3 genotype III currently circulating in Thailand clusters with lineage-C viruses from South Asia (India and Pakistan) and from other areas in Southeast Asia (Singapore, Laos, and Viet Nam) where the virus had been detected; this cluster was independent of the lineage-A viruses (recovered from Sri Lanka, Malaysia, and Singapore) and the lineage-B viruses obtained in the Americas.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of Thailand, DENV-3 genotype III also has been disseminated to other countries in Asia. DENV-3 genotype III was isolated as a minor genotype in Laos in 2012–2013 [ 76 ], and was first observed in Vietnam in 2013 [ 77 ], in Singapore in 2013 [ 78 ], and in Malaysia in 2008–2010 [ 74 ]. Our study revealed that the DENV-3 genotype III currently circulating in Thailand clusters with lineage-C viruses from South Asia (India and Pakistan) and from other areas in Southeast Asia (Singapore, Laos, and Viet Nam) where the virus had been detected; this cluster was independent of the lineage-A viruses (recovered from Sri Lanka, Malaysia, and Singapore) and the lineage-B viruses obtained in the Americas.…”
Section: Discussionmentioning
confidence: 99%
“…sequence for DENV-3 and two studies that reported partial E-NS1 sequences for DENV-2, have examined the genetic characteristics of neurotropic DENV. All of these DENV were isolated from CSF samples [8,[42][43][44][45]. To our knowledge, this is the first report to describe the complete genome and the molecular and virological characteristics of DENV-2 isolated from CSF samples from fatal and non-fatal dengue case-patients with neurological manifestations.…”
Section: Plos Onementioning
confidence: 93%
“…To our knowledge, this is the first report to describe the complete genome and the molecular and virological characteristics of DENV-2 isolated from CSF samples from fatal and non-fatal dengue case-patients with neurological manifestations. Compared with other dengue serotypes, DENV-2 and DENV-3 appear to be more frequently associated with encephalitis and other neurological manifestations, regardless of whether it is primary or secondary infections [43,45]. In a meta-analysis examining the severity of dengue during primary or secondary infection with different DENV serotypes, secondary infections with DENV-2 were reported to be associated with severe cases [46].…”
Section: Plos Onementioning
confidence: 99%
“…Although the early diagnosis of dengue fever is usually based on detection of viremia, there are several reports of DENV in cerebrospinal fluid [6], saliva and urine [7]. We are aware of only one case report of the isolation of dengue virus from a respiratory specimen [8].…”
Section: Introductionmentioning
confidence: 99%